Relatos y retratos sobre el tocado andalusí en el Río de la Plata : entre el hablar hispánico y el habitar indumentario arábigo - Redondo, María de los Ángeles (2022)
This work is dedicated to the study of the use, consumption and recovery of the Andalusian headdress in the Río de la Plata, understanding it as a product of Latin-Arabic intercultural design, as a cultural continuation of Hispanic speaking and Arabic living, which is constituted as a differentiating component of the local female costume.\nDespite having an unquestionable validity as a distinctive symbol of certain sectors of Argentine society -after having been retaken and resinified during the 20th and 21st centuries- the study of this clothing has the most absolute indifference to part of the costume historians.\nIn this sense, our exploratory inquiries about the history of the local costume reveal an important thematic vacancy. Scholarly void that contrasts with the abundance of period documents that testify about its consumption and recovery.\nDisproportion that deserves a work that explores possible answers to the questions that this scenario raises, systematizing at the same time, the specific information available on the subject, especially taking into account the high degree of complexity and dispersion that it presents.\nLikewise, as the meaning assigned by the Dictionary of the Royal Spanish Academy to the Andalusian term does not allow its application as an artistic category detached from the "Arabic" or "Islamic", we pose as a question and starting premise of our work if it is possible to have a perception determined on a culture and a different one of the design products attributed to it.\nIf we take into account that, as Eco (1968) points out, the attribution of meanings that govern the design operation will vary according to the reading codes used, we then have that the local use of "Andalusian" clothing will be conditioned by the variation of the ways of perceiving or interpreting the "Arabic" or "Islamic" that the perceptions and discourses that refer to it has.\nBy extension, it is possible to suspect that this consumption and recovery as well as its identification or not, were conditioned by the variation in the ways of perceiving or interpreting the "Andalusian" by the portraits and stories that refer to it.\nTherefore, considering the prevailing historiographic silence, it is possible to infer the presence of some type of ideological incidence around the interpretation of the consumption and recovery of the Andalusian headdress in the Río de la Plata.\nThus, we assume as a hypothesis that what is proposed as the starting premise of our work is not possible because it does not seem possible to have a perception about Andalusian design objects independent of those about Arabs and Islam, as well as having a representation of both independent of Orientalism (Said, 1978). Much less presume that this does not affect the consumption, recovery, perception and interpretation of clothing identifiable as "Andalusian".